2017
DOI: 10.2337/db16-1060
|View full text |Cite
|
Sign up to set email alerts
|

Neu5Gc and α1-3 GAL Xenoantigen Knockout Does Not Affect Glycemia Homeostasis and Insulin Secretion in Pigs

Abstract: Xenocell therapy from neonate or adult pig pancreatic islets is one of the most promising alternatives to allograft in type 1 diabetes for addressing organ shortage. In humans, however, natural and elicited antibodies specific for pig xenoantigens, α-(1,3)-galactose (GAL) and -glycolylneuraminic acid (Neu5Gc), are likely to significantly contribute to xenoislet rejection. We obtained double-knockout (DKO) pigs lacking GAL and Neu5Gc. Because Neu5Gc mice exhibit glycemic dysregulations and pancreatic β-cell dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…69 CMAH and GGTA1 double knockout pigs do not appear to have altered insulin secretion. 70 Consistent with previous studies, our data indicate a higher number of GGTA1 transcripts in NPI versus API, but also a higher number of CMAH transcripts. 29 However, VWF has significantly higher expression in API and has been linked with graft dysfunction due to platelet activation.…”
Section: Discussionsupporting
confidence: 93%
“…69 CMAH and GGTA1 double knockout pigs do not appear to have altered insulin secretion. 70 Consistent with previous studies, our data indicate a higher number of GGTA1 transcripts in NPI versus API, but also a higher number of CMAH transcripts. 29 However, VWF has significantly higher expression in API and has been linked with graft dysfunction due to platelet activation.…”
Section: Discussionsupporting
confidence: 93%
“…104,136,142,145 Currently, it seems that both the αGal and Neu5Gc-glycans limit the potential of xenotransplantation, as recently reviewed elsewhere, 103,104,[146][147][148] and generation of double-knockout animals deficient in both the CMAH and GGTA1 genes seems to be promising. 139,147,[149][150][151]…”
Section: Con S Equen Ce S Of Neu5g C and Anti -Neu5g C Antibod Ie Smentioning
confidence: 99%
“…More recently, double knockout of GGTA1 and of CMAH (cytidine monophosphate-N-acetylneuraminic hydroxylase) responsible for Neu5Gc (N-glycolylneuraminic acid) synthesis was shown to further decrease porcine islet antigenicity compared to GGTA1 knockout alone [22]. A recent paper by Salama et al showed that such a double knockout in porcine beta cells is possible without affecting islet function both in vivo and in vitro [23]. Another porcine carbohydrate antigen produced by beta-1, 4-N-acetyl-galactosaminyl transferase 2 (B4GALNT2) was identified by screening cDNA from GGTA1…”
Section: Modification Of Donor Pigs To Mitigate the Immunementioning
confidence: 99%